A Calculus of Mobile Agents - Fournet, Cédric; Gonthier, Georges; Levy, Jean-Jacques; Maranget, Luc; Rémy, Didier (7th International Conference Pisa, Italy, August 26-29, 1996 Proceedings, 1996)
We introduce a calculus for mobile agents and give its chemical semantics, with a precise definition for migration, failure, and failure detection. Various examples written in our calculus illustrate how to express remote executions, dynamic loading of remote resources and protocols with mobile agents. We give the encoding of our distributed calculus into the join-calculus.